MENDIDIK ANAK (EDUCATING CHILDREN) - Sri Wahyuni; Yan Kristianus Kadang (QUAERENS: Journal of Theology and Christianity Studies, 2019)
This study also aims to examine and analyze the tendency of the church's understanding of educating children, the tendency of the indicators that most strongly determines the formation of the congregation's understanding of educating children, testing and analyzing which backgrounds the respondent has that causes differences in congregational understanding about educating children. The population in this study was the church members who attended the Indonesian Trumpet Christian Church in the Bethlehem Grogol Permai Satellite Church. The number of congregations who attend the Church of the Indonesian Trumpet Christian Church Bethlehem Permai Grogol Satellite numbered 200 people. A sample of 158 people were taken at random. The results showed that the tendency of the congregation's understanding of educating children in the Trumpet Christian Church of Indonesia, the Grogol Permai Bethlehem Satellite Church was in the category of congregations understanding about educating children significantly at α less from 0.05. There is the strongest influence that shapes the congregation's understanding of educating children in the Trumpet Christian Church in Indonesia. The Grogol Permai Bethlehem Satellite, the Teaching indicator, X2, is at a significant level at α less from 0.05, which is 497.36 times the increase that occurs in the church's understanding of educating children from the original condition. Penelitian ini juga bertujuan untuk menguji dan menganalisis kecenderungan pemahaman jemaat mengenai mendidik anak, kecenderungan indikator yang paling kuat menentukan terbentuknya pemahaman jemaat mengenai mendidik anak, menguji dan menganalisis manakah latar belakang yang dimiliki responden yang menyebabkan adanya perbedaaan pemahaman jemaat mengenai mendidik anak. Populasi dalam penelitian ini adalah jemaat yang bergereja di Gereja Kristen Sangkakala Indonesia Jemaat Betlehem Satelit Grogol Permai. Adapun Jumlah jemaat yang bergereja di Gereja Kristen Sangkakala Indonesia Jemaat Betlehem Satelit grogol Permai berjumlah 200 orang. Sampel sebanyak 158 orang yang di ambil secara acak. Hasil penelitian menunjukkan bahwa kecenderungan pemahaman jemaat mengenai mendidik anak di Gereja Kristen Sangkakala Indonesia Jemaat Betlehem Satelit Grogol Permai berada pada kategori jemaat paham mengenai mendidik anak secara signifikan pada α lebih kecil dari 0,05. Terdapat pengaruh terkuat yang membentuk pemahaman jemaat tentang mendidik anak di Gereja Kristen Sangkakala Indonesia Jemaat Betlehem Satelit Grogol Permai yaitu indikator Mengajar, yaitu X2 berada pada taraf signifikan pada α lebih kecil dari 0,05 yaitu sebesar 497.36 kali peningkatan yang terjadi di dalam pemahaman jemaat mengenai mendidik anak dari kondisi semula.